Which CEO Characteristics Have Effect Towards Influencing CSR Activities in Family Business: A Study of Emerging Market Firms - Sathasivam, Gokul (2017)
This study was carried in-order to find out the effects of CEOs in family firms towards CSR in emerging market. Family businesses are dominant players in global economies. Using the data of family firms in a setting of weak institutions resulting from a deficiency of market-based management skills, we ask which CEO characteristics matter? The involvement by family members as CEOs is a common practice in family businesses. However, we find that family CEOs reduce firm value, indicating higher potential expropriation of minority shareholders or possible lower competency of family CEOs relative to professionals. On the other hand, research on corporate social responsibility (CSR) has traditionally focused on managerial discretion and stakeholders’ influence. This study extends current research by addressing the effect of family firm’s CEO on CSR performance, namely, CSR strengths and concerns. Based on agency theory, stewardship theory and the socioemotional wealth perspective, we propose that family firm CEOs are more likely to value CSR performance. We tested our hypotheses using a sample of 91 firms from 2010 to 2014 and found general support for our hypotheses. A higher percentage of family owned equity and the presence of a family CEO are found to increase CSR strengths, whereas CEO duality, CEO experience, CEO education, CEO network and Foreign CEO proved to have negative effect towards influencing CSR activities. Although CEO’s foreign education proved to have a significance effect towards driving CSR activities. Our analysis suggest, family CEO will have a positive effect in family business and also will ensure that firm engages in CSR activities in-order to build a reputable firm image and also protect local community.